2005
DOI: 10.1007/s10584-005-5923-2
|View full text |Cite
|
Sign up to set email alerts
|

On the Climate Impact of the Local Circulation in the Itaipu Lake Area

Abstract: The impact of the Itaipu Lake on the climate and local circulation is investigated here using the meteorological information available in the area. The Itaipu Lake is an artificial water reservoir of 1460 km 2 (approximately 170 km by 7.5 km), formed in 1982 as part of the Itaipu Power Plant. It is situated on the Brazil-Paraguay frontier, in the central portion of Parana River Valley. The analysis of the available meteorological data (air and water temperatures, air relative humidity, precipitation and radios… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 27 publications
2
16
0
1
Order By: Relevance
“…The inspection of the topographical map of Itaipu valley (Stivari et al, 2005), suggests that the topography of the transition zone favours a flow increasing (Tucci, 2002), maximising the contribution of allochthonous material to the reservoir. In the terrestrial area adjacent to the transition zone there are numerous rural properties with rearing pigs and their waste are discarded / washed away without any treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The inspection of the topographical map of Itaipu valley (Stivari et al, 2005), suggests that the topography of the transition zone favours a flow increasing (Tucci, 2002), maximising the contribution of allochthonous material to the reservoir. In the terrestrial area adjacent to the transition zone there are numerous rural properties with rearing pigs and their waste are discarded / washed away without any treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In tropical dams, the increase in the minimum air temperature and the decrease in the maximum air temperature follow the same trend, although the diurnal range remains almost constant throughout the year (Stivari et al 2005). In the subarctic Great Lakes, the minimum air temperature increased throughout the year, although the winter maximum air temperature decreased, and the diurnal range was larger in summer than in winter (Hinkel and Nelson 2012).…”
Section: Slight Decrease In the Daytime Air Temperaturementioning
confidence: 69%
“…Sacks et al (2009) reported that irrigation changed the local air temperature by increasing evaporation. Additionally, several explanations have been offered regarding the effect of dam lakes on the local climate from observational studies (Stivari et al 2005). In Ghana, downstream of the Akosombo Dam, the air temperature changed as the river flow decreased (Gyau-Boakye 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sun et al (1997) investigated diurnal and seasonal variations of lake-induced atmospheric circulation over three lakes by using aircraft observation data. Stivari et al (2005) analyzed local circulation in a lake area by using available meteorological data. These studies examined local circulations induced by water bodies with width of a few kilometers.…”
Section: Introductionmentioning
confidence: 99%